Salpa thompsoni in the Indian Sector of the Southern Ocean: Environmental drivers and life history parameters. (April 2020) - Kelly, Paige; Corney, Stuart P.; Melbourne-Thomas, Jessica; Kawaguchi, So; Bestley, Sophie; Fraser, Alexander; Swadling, Kerrie M.
Abstract: The Southern Ocean ecosystem is thought to be experiencing a long-term increase in Salpa thompsoni . Uncertainty surrounds the environmental drivers behind variable S. thompsoni abundances, particularly within the East Antarctic region. In this study, S. thompsoni populations were sampled in the Indian Sector of the Southern Ocean, as part of the January–February 2016 Kerguelen Axis voyage. These recent data were compared against historical density records in the broader Kerguelen Plateau region from voyages during 1985–2006. Results show that 2016 maximum S. thompsoni densities across the Kerguelen Plateau were higher, and more southerly located, than those previously sampled in the area. The highest 2016 S. thompsoni abundances exceeded 2500 individuals 1000 m -3 and were located between the Southern Boundary of the Antarctic Circumpolar Current and the Southern Antarctic Circumpolar Current Front. The life-stage composition of S. thompsoni comprised approximately 90% aggregates (blastozooids) and 10% solitaries (oozoids). Generalised Additive Models associated low chlorophyll- a concentration and low solar elevation (outside of peak daylight) with higher S. thompsoni abundances. In addition, elevated abundances occurred in locations from where the sea ice retreated at least eight weeks previously. These abundance-environment relationships are consistent with results from several previous surveys in the region and the West Antarctic. Due to the complex life cycle of S. thompsoni, and the unpredictability of their distribution patterns, multi-seasonal and multi-year surveys are needed to confirm whether the 2016 distribution patterns are indicative of a long-term increase or southerly shift in abundances. The new information from this study provides much needed baseline abundance and distribution data (which can be used to assess future change in a currently understudied oceanographic region) on a species capable of shaping the future ecosystem structure and function in the Indian Sector of the Southern Ocean.